2020
DOI: 10.1051/0004-6361/202038712
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting high spatial resolution line observations of planet-forming disks with gaps and rings: the case of HD 163296

Abstract: Context. Spatially resolved continuum observations of planet-forming disks show prominent ring and gap structures in their dust distribution. However, the picture from gas observations is much less clear and constraints on the radial gas density structure (i.e. gas gaps) remain rare and uncertain. Aims. We want to investigate the importance of thermo-chemical processes for the interpretation of high-spatial-resolution gas observations of planet-forming disks and their impact on the derived gas properties. Meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 91 publications
10
42
1
Order By: Relevance
“…In HD 163296, the derived CO surfaces, and in particular, the measured depths of vertical substructures, in HD 163296 most closely match the models of Rab et al (2020) that include deep gas gaps, i.e., similar depletion as for the dust, at the locations of the observed millimeter continuum gaps. Similarly, the gas gap models (versus that of CO depletion) from Calahan et al (2021) are better able to reproduce the Z81 dip in the C 18 O emission surface.…”
Section: Origins Of Vertical Substructuressupporting
confidence: 58%
See 1 more Smart Citation
“…In HD 163296, the derived CO surfaces, and in particular, the measured depths of vertical substructures, in HD 163296 most closely match the models of Rab et al (2020) that include deep gas gaps, i.e., similar depletion as for the dust, at the locations of the observed millimeter continuum gaps. Similarly, the gas gap models (versus that of CO depletion) from Calahan et al (2021) are better able to reproduce the Z81 dip in the C 18 O emission surface.…”
Section: Origins Of Vertical Substructuressupporting
confidence: 58%
“…Localized vertical substructures are observed in many of the emission surfaces derived from the MAPS data. The properties of these substructures, namely their radial locations, widths, and depths, provide important constraints that are necessary for detailed thermochemical modelling (e.g., Rab et al 2020;Calahan et al 2021). In the following subsections, we identify and catalogue all substructures present in the derived emitting layers and compare them with the gas temperature profiles, and with substructures observed in the millimeter continuum and CO line emission.…”
Section: Substructures In Emission Surfacesmentioning
confidence: 99%
“…Additionally, part of the 13 CO and C 18 O emission from the back side of the disk can be absorbed by dust particles located in the midplane (Isella et al 2018;Rab et al 2020). This process can theoretically delete up to half of the emission if the line is optically thin and the dust highly optically thick.…”
Section: Morphology Of the Dust And Gas Emissionmentioning
confidence: 99%
“…In particular, Teague et al (2018) obtained fractional deviations of a few percent in the region occupied by the second and third planet, between ≈ 80 and ≈ 200 au, in good accord with the results presented in the Figure (note that we refer to the unperturbed velocity 𝑱 * 𝜙 rather than to the Keplerian velocity 𝑣 Kep ). Rab et al (2020) also performed a detail analysis of the rotational velocity deviations of the ring region and arrived at very similar conclusions (see total fractional variations in their Figure 7). Pinte et al (2018) reported deviations at ≈ 260 au amounting to ≈ 15% of the local Keplerian velocity, which they modelled as induced by a 2 𝑀 J planet orbiting at that distance.…”
Section: Figurementioning
confidence: 53%
“…The right panel of Figure 2 shows the ratio 𝑱 𝜙 /𝑱 * 𝜙 , averaged in azimuth around the star. Deviations of the gas rotation profile from a Keplerian pattern have been reported for HD 163296 by several groups (e.g., Teague et al 2018;Pinte et al 2018;Rab et al 2020), based on observations of CO spectral features. In particular, Teague et al (2018) obtained fractional deviations of a few percent in the region occupied by the second and third planet, between ≈ 80 and ≈ 200 au, in good accord with the results presented in the Figure (note that we refer to the unperturbed velocity 𝑱 * 𝜙 rather than to the Keplerian velocity 𝑣 Kep ).…”
Section: Figurementioning
confidence: 65%